The Effect Of Audiovisual Learning Media On Elementary Students’ Understanding Of Least Common Multiple And Greatest Common Divisor - Puji Astuti; Muhajir; Nuril Huda (Celebes Journal of Elementary Education, 2026)
The research aims to analyze the effects of audiovisual media on sixth-grade students' learning about LCM & GCF in UPTD SDN Gili Barat Elementary School, Kamal District. This research utilized a quantitative methodology employing a nonequivalent control group quasi-experimental design. The study population consisted of 275 students, from which a sample of 40 was selected, including 20 students in the control group and the other 20 in the experimental group. To determine people's understanding of both LCM and GCF, we administered multiple-choice examinations consisting of 10 questions each. The data were analyzed using an independent samples t-test and MANOVA. The control group achieved an average LCM understanding score of 57.50, whereas the experimental group scored slightly higher at 57.75. Statistical analysis using an independent t-test indicated a significant difference between the groups (p < 0.05), indicating that audiovisual media had a statistically significant and large effect on LCM comprehension. The mean score of GCF understanding in the control group was 57.50, while the experimental group obtained a mean score of 57.75. Although the difference between the two groups was relatively small, the MANOVA test indicated a statistically significant effect with a significance value of 0.021. In addition, the analysis reported a target significance level of 0.018 and an observed power of 1.000. This implies that audiovisual media impacted the students' understanding of the LCM and GCF systematically. The use of audiovisual media was thus effective in making students understand abstract ideas in arithmetic by using more concrete and immersive audiovisual experiences.